PEDIATRIC MIGRAINE EQUIVALENTS. CHILDHOOD PERIODIC SYNDROMES. A REVIEW OF LITERATURE AND THE AUTHORS’ CLINICAL OBSERVATIONS - A. E. Ponyatishin; A. B. Pal’chik; V. V. Privorotskaya; O. I. Glebovskaya (Русский журнал детской неврологии, 2016)
Childhood periodic syndromes are a group of functional states occurring at an early age, including in the first year of life, which are pre sently considered as equivalents or precursors for further migraine. Insufficient coverage of the problem in the Russian literature, the paroxysmal occurrence and periodic recurrence of these states are a frequent cause of readmissions, numerous, sometimes invasive studies, misdiagnoses, and, as a consequence, the use of aggressive, pathogenetically unsound therapy, which ultimately affects quality of life in a child. The review article highlights the basic issues of the epidemiology, etiology, pathogenesis, clinical manifestations of major forms of childhood periodic syndromes, as well as approaches to their diagnosis, treatment, and prediction. To familiarize a wide range of specialists, not only neurologists, with these conditions in children will, of course, reduce the overdiagnosis of various more serious diseases.